Antecedents of behavioural intention and prioritization of restaurant attributes affecting customer satisfaction at casual dining restaurants in the Klang Valley, Malaysia - Ebrahimian, Mahshid (2019)
The ultimate goal of any business especially in hospitality industry is customer satisfaction, which is defined as a customer’s perception of the performance of a product or service, with regard to his/her expectations. It is further identified as an important antecedent to repurchasing, loyalty, positive word-of-mouth, and long-term relationships with the company. As a result, restaurant managers have changed their focus to the characteristics of customer behavioral intentions rather than just satisfaction. Therefore, investigating the most important and affective attributes that lead to customer satisfaction and positive behavioral intentions is critical for restaurant success. Despite the extensive literature in the restaurant segment, there are gaps in the analysis of customer satisfaction and behavioral intentions in terms of a comprehensive model including service quality, food quality, physical environment quality, price, and technology along with the attitude towards behavior, subjective norm and perceived behavioral control. Therefore, the current study will fill the gap by considering aspects that were not included in the previous researches. Moreover, previous studies have applied the traditional view of satisfaction indicating that the attribute performance has a symmetrical correlation with satisfaction. While, the nonlinear and asymmetric relationships between attribute performance and satisfaction proposes that the performance of all attributes do not have equal and same effect on customer satisfaction. Thus, integrating the asymmetric effects of restaurant aspects on satisfaction allows restaurant managers to identify features that are more likely to trigger satisfaction or dissatisfaction. Therefore, in this study, the structural equation modeling (SEM) was used to evaluate the relationships between customer satisfaction, behavioral intentions and the independent variables of service quality, food quality, physical environment, price and technology. The effect of restaurant attributes along with the effect of TPB constructs on behavioral intentions were also examined. In addition, the Importance–Performance Analysis (IPA) approach was used to assess the keydrivers of customer satisfaction and their asymmetric effects. Data for this quantitative study was collected from 400 customers at casual dining restaurants located in KLCC and Pavilion shopping malls. Findings showed that there is a statistically significant relationship between customer satisfaction and each of the independent variables. It also revealed that customer satisfaction significantly mediates the relationship between restaurant attributes and behavioral intentions. Furthermore, there is a statistically significant positive association between satisfaction and behavioral intentions. The IPA results showed that restaurant attractiveness, employee knowledge, fair menu price and availability of smart phone application play the role of basic factors (dissatisfiers) in casual dining restaurants, and that the casual dining outlets should improve these important areas to create satisfied customers. In addition, restaurant cleanliness, bill accuracy, safe transaction, polite and experienced employees, food taste and quality, ambient conditions, seating comfort, appropriate portion size, and Wi-Fi availability are considered as the performance factors (hybrids), which appear to be key attributes for casual dining restaurants’ success. Almost all empathy parameters of the service-related attributes, menu variety, price, food presentation, restaurant colour, dining privacy and direction’ sings are considered as the excitement factors (satisfier) in casual restaurants, which are typically unexpected by customers. Overall, this study suggested that basic factors and performance factors are the pivotal aspects to create satisfied customers and positive post-dining behavioral intentions. Therefore, results of this study shed light on prioritizing focus and resource allocation by the casual dining restaurant managers based on attributes contributions to customer satisfaction and behavioral intentions in order to generate higher profit for the restaurant. Besides, these findings can also be used by restaurant managers to set customer-oriented guidelines and strategies in order to make the casual dining outlet a more popular choice.